Chemical constituents and fiber dimensions of Malaysian Native Wood - Latna Mageshwary A/P Thanakodi (2016)
The demands for wood and wood-based products are likely to increase in the future as it contributes in many applications. It is also important to study the chemical constituents and ﬁber dimensions of the wood to determine its potential utilization. The chemical constituents (holocellulose, cellulose, hemicelluloses, lignin and extractives) and the ﬁber dimensions (ﬁber length, ﬁber width and lumen diameter) of Sesbania grandiﬂora have been determined in this study. The standard methods were used to determine each chemical constituent. Soxhlet extraction was performed for the determination of extractives and deligniﬁcation method was conducted to obtain the holocellulose content. Kurschner hoffner’s method and drying method were carried out for the determination of cellulose and ash content respectively. Simple microscopic and Scanning Electron Microscope (SEM) studies were carried out for the determination of ﬁber dimensions. The results revealed that stalks of Sesbania grandiﬂora contain 6.20% of extractives, 79.75% of holocellulose, 14.05% of lignin, 39.0% of cellulose, 40.75% of hemicellulose and 12.05% of ash respectively. The ﬁber dimension results showed that the Sesbania grandzflora stalks has ﬁber length of 0.00256mm, ﬁber width ranging from 13.25µm to 17.83µm and lumen diameter of 0.22µm.